UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG PADA ANAK KELAS 6 SD SIDOMULYO DESA KANDANG SAPI KECAMATAN JENAR KABUPATEN SRAGEN - Nisa Fahera, Qoirun; Kuni, Fatonah (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2023)
Elementary school children are in the right golden age to provide educational stimulation. One aspect of development is the Congnitive aspect . Children's congnitive abilities can be developed by counting. Numeracy skills are important, both for performing calculations quickly and solving arithmetic. Many found that the numeracy skills of children in Sidomulyo Hamlet, Kandang Sapi, Jenar, Sragen are very low even at the upper class level. This community service aims to improve the ability to calculate mathematics. This community service activity uses the Conservation method which is carried out by conducting interviews with children in Sidomulyo Hamlet and continued with the method of implementing activities. The purpose of this tutoring is to increase children's enthusiasm in learning, especially mathematics subjects, break the assumption that mathematics is a difficult and boring subject, and provide innovations or ways of counting that are fun and easy to apply to problems. Good numeracy skills are not only useful when you are still in school, even in everyday life, it is inseparable from counting activities.